Efforts To Increase Learning Results In Learning Squat Style Loose Through Video Learning Jumping Rope Exercise For V Grade Students Mis Lubuk Girl - Rio Asran Syah Putra; Martiani Martiani; Mariska Febrianti (Sinar Sport Journal, 2021)
This study aims to improve the learning of the squat style long jump in fifth grade students of MIS Lubuk Gadis. This type of research is Classroom Action Research (CAR) consisting of four stages in each step (planning, implementation, observation, and reflection). The research subjects in this study were all students of class V MIS Lubuk Gadis, totaling 25 students. The results showed that the action by watching videos of jumping rope exercises carried out in 3 cycles with each cycle of 2 meetings was proven to be able to improve the Efforts to Improve Squat Style Long Jump Learning Outcomes Through Learning Videos of Class V MIS Lubuk Girls Jump Rope Exercises. In the first cycle of the first meeting there was an increase in completeness of 28%, namely 7 students completed and 18 students did not complete (72%). Then in the first cycle of the second meeting there was an increase in completeness by 36%, namely 9 students completed and 36 students did not complete after that in the first two cycles there was an increase in completeness by 52%, namely 13 students completed and students did not completed 12 students (48%). In the second cycle of the second meeting there was an increase in completeness by 64%, namely 16 students completed and 9 students did not complete (36%).